My IEP: A Student-Directed Individualized Education Program Model. Issue 4 (2nd October 2017) - Royer, David J.
ABSTRACT: Students with disabilities need to be more involved in planning and presenting individualized education program (IEP) meetings, and teachers need an effective, efficient curriculum to teach students how. My IEP curriculum uses folding graphic organizers to teach students to self-direct IEP meetings, targeting self-advocacy and self-determination to combat student apathy toward and passive participation in IEPs. Students who received My IEP ( n = 25) spoke on average for 36.78% of IEP meeting time, while comparison group students ( n = 14) spoke on average 2.15%. My IEP students recalled significantly more IEP knowledge and had shorter meetings. School faculty and staff were significantly more satisfied with My IEP meetings.